2019
DOI: 10.18203/2320-6012.ijrms20195924
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of supraglottic airway devices Baska mask and ProSeal-laryngeal mask airway in short gynaecological procedures

Abstract: Background: Baska Mask® (BM) a newer Supraglottic Airway Device (SAD) considered to cause low incidence of Postoperative Pharyngolaryngeal Complications (POPC). This study was designed to assess efficacy, safety and early and late POPC between BM and commonly use ProSeal LMA (PMLA).Methods: Patients between 18 to 60 years of age undergoing elective short gynecological procedures were randomized into two groups, to receive ventilation with either BM (group 1, n=50) or an PMLA (group 2, n=50).Results: There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The ease of insertion between the two groups was comparable with a p-value of 0.284. Our results were similar to the findings of Kachakayala et al They also found the ease of insertion comparable between these two devices [ 6 ]. In the BM group, 23.33% of patients required manipulation, while 10% of patients required manipulation in the LMA-P group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ease of insertion between the two groups was comparable with a p-value of 0.284. Our results were similar to the findings of Kachakayala et al They also found the ease of insertion comparable between these two devices [ 6 ]. In the BM group, 23.33% of patients required manipulation, while 10% of patients required manipulation in the LMA-P group.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that the mean time for insertion in the BM group (25.33 ±3.62 seconds) was comparatively shorter than that in the LMA-P group (28.77 ±6.6 seconds) (p=0.004), which is very similar to the findings in other studies [5][6][7][8][9][10]. The reason behind the quick and easy insertion of BM may be attributed to its manufacturing design, which includes a cuffless membrane and a tab to increase the palatopharyngeal curve to assist insertion.…”
Section: Discussionsupporting
confidence: 90%
“…A cuffless membrane of BM with an additional tap can be pulled to increase the curvature, aiding its insertion fast and efficiently into the oropharyngeal cavity [9]. Several studies over the years have favored our findings [10,11]. A study by Balwinderjit et al found that, in terms of mean insertion time, the BM (14.25±3.82 seconds) took less time to insert than PLMA (22.01±2.64 seconds) [3].…”
Section: Discussionmentioning
confidence: 61%
“…The laryngeal mask airway and endotracheal tube are the classic tools to management the airway of children receiving general anesthesia. In a systematic review and meta-analysis covering 1,433 patients undergoing laparoscopic surgery, LMA was found to permit more stable perioperative haemodynamic parameters and less stress than endotracheal intubation [11]. For ophthalmic surgery in pediatric patients, the use of an LMA is also bene cial for less uctuation in intraocular pressure [12].…”
Section: Discussionmentioning
confidence: 99%